Implementasi Low Power Wearable Device Sebagai Heart Rate Monitor Dengan Metode State Machine - Ihsanurrahim Ihsanurrahim; Dahnial Syauqy; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Health is most important thing for human being, health can cause to daily activity. Health can be measured by measuring one of four vital sign which is heartbeat will be the focus for now. Using wearable device measuring heartbeat can be done easily. In order for the device to support daily activities the device must have a low power mechanism for conserve power consumption to work in long term with battery power. State machine and ATmega328p power down sleep feature is implemented into a prototype system that works as heartbeat monitor for sensing heartbeat, display data, and send data to smartphone device. Test on prototype provide a conclusion that prototype already working properly. Prototype giving 3.79 % error result for pulse sensor reading test at normal condition and 7.91% after sport condition, which means pulse sensing is working properly. Prototype can reduce power consumption by reducing current by 23.78 mA or 75.06 % from 31.68 mA with implementing state machine and power down sleep for it low power mechanism. For it performance prototype can works effectively up to 12-meter range and prototype wake time from sleep until reading sensor and sending data require only 0.0508 second.